Parking design in the tropics - Galingan, Zenaida C. (Quezon City College of Architecture, University of the Philippines, Diliman, 1994)
In designing an open parking in a tropical country like the Philippines, one encounters problems that can not be avoided especially those which are associated with climate, like the blinding glare and the consuming heat that a vast pavement produces. Added to this is the visual monstrosity that it creates not to mention broken pavements caused by tree roots and many other unforeseen difficulties. As such, this paper aims to find solutions that will soften and alleviate these problems, in order to produce a parking that will be adaptable to the tropics. Subject to project study is the innovative parking area of a prestigious corporation's head office complex in contrast with the conventional parking design. (For reason of security, the name of the corporation cannot be mentioned).
Thesis (Master of Tropical Landscape Architecture)--University of the Philippines, Diliman.
Keywords: Parking lots -- Landscape architecture; Parking lots